Desafios e possibilidades na autoformação do gestor acadêmico de instituições de educação superior privadas - Basso Júnior, José Norberto (2011)
This study aimed to understand and reflect on the criteria for nomination and appointment of academic administrators in higher education institutions (HEI) small private, located in the Midwest in the state of São Paulo, aiming to uncover challenges and possibilities of managers experienced in daily life. It is hypothesized that the lack of criteria for the selection and appointment of managers in private institutions makes the choice to be decided by the maintainers, who generally opt for the promotion of staff's own institutional framework, requiring the self-training in the management process . From this perspective, the research problem rests on the need to understand how they are nominated and selected academic managers of private higher education, his arrival in office in HEI and how to develop the self-formative process in the job for them to exercise the functions of management. The research presents an approach supported by qualitative interviews, and had as the driving public policy analysis and discussion of new scenarios of Brazilian higher education. Told primarily with theoretical support Galvani (2002), Lebanon (2004), Swain (2004), Mello (2008), Boaventura de Souza Santos (1999) and (2005), Santos Neto (2009), Tachizawa (2006), Anisio Teixeira (1989), Trigueiro (2000) and (2002), Valois (2007), Visentin (2009) and Vasconcellos (2007). As the search results, it was observed that: a) the appointment of managers derived from the encouragement of their own workforce HEIs surveyed institutions being perceived lack of clarity and institutional criteria established for the promotions and appointments, and the absence of definitions public policies that regulate or govern this situation, b) knowledge of public policy is essential tool for managing performance, contributing significantly to the formation of the manager, c) there is recognition of the respondents that the training manager is through a self-formative process during the management itself, being built through this process of interaction with institutional documents and policies of public education, relations with the academic environment, in mediations between faculty, students and technical and administrative staff of the IES.